Studi Pengaruh Magnetic Arc Blow Pada Hasil Las TIG Baja AISI 1021 - Juliana Anggono; Juliana Anggono; Luciana Hariani Kusuma (Jurnal Teknik Mesin (Sinta 3), 1999)
Discontinuities and size of the weld deposit are affected by many factors. Magnetic arc blow is one of the factors that one may not be aware of. Magnetic arc blow was studied in this research with the ground position and welding current were varied. The discontinuities and size of the weld deposit were observed and measured by taking specimens of the carbon steel of AISI 1021 welded by TIG welding process using argon as protective gas. Macro photographs and data of the size of the weld deposit show magnetic arc blow has strong influence on the size of the weld on the first cut section. This specimen was welded by using 200 Ampere with the ground placed in the starting point of the welding process. Undercut and incomplete penetration are commonly found as discontinuities in all cut sections of the specimens. While porosities occur mainly in the first section with high current. It 's believed that these discontinuities occur due to the lack of shielding by the protective gas caused by very strong arc blow around the melt. Tungsten inclusions are also the common discontinuities to take place, they are found more when welding using high current (200 A). Their occurrence is because of the melting of the tip of the tungsten electrode caused by the high heat input.. At the end of the weld, crater and spatter are always found. Backward arc blow are very strong at the end of the process that arises these defects. Abstract in Bahasa Indonesia : Cacat dan bentuk deposit hasil las busur listrik dipengaruhi oleh banyak faktor. Salah satunya yang sering tidak diketahui adalah adanya pengaruh magnetic arc blow. Magnetic arc blow dengan variasi penempatan ground dan besar arus las dipelajari dalam penelitian ini dengan mengamati pengaruhnya terhadap cacat dan mengukur penampang deposit las yang dihasilkan. Proses las yang diamati adalah las TIG pada baja AISI 1021 dengan gas pelindung argon dengan polaritas lurus (DCSP). Hasil foto makro dan pengukuran menunjukkan magnetic arc blow berpengaruh kuat pada ukuran dan bentuk deposit las pada potongan pertama menggunakan arus 200 A serta penempatan ground pada awal proses pengelasan. Cacat las undercut dan incomplete penetration adalah cacat yang umum dijumpai pada semua potongan. Sedangkan dominasi cacat porositas pada potongan pertama lasan dengan arus 200 A diduga karena kurangnya ruang perlindungan gas dalam daerah las. Inklusi tungsten banyak terjadi pada arus 200 A karena melelehnya ujung elektroda tungsten akibat input panas tinggi. Pada akhir pengelasan selalu dijumpai crater dan percikan. Kedua jenis cacat ini juga diyakini disebabkan oleh backward arc blow yang cukup besar terjadi pada akhir proses lasan. Kata kunci : magnetic arc blow, undercut, incomplete penetration, porositas, crater